Item Analysis of Arabic Midterm Exam Class X SMK Muhammadiyah 4 Yogyakarta Based on Classical Theory with R Program - Syaikha Dziyaulhaq Zein*; Ana Taqwa Wati; Anugrah Arya Bakti (Riwayat: Educational Journal of History and Humanities, 2023)
This study produces the results of the analysis of Arabic Language Midterm Exam items at SMK Muhammadiyah 4 Yogyakarta stating that the report data obtained from the results of mathematics tests with 25 items and 88 participants as shown in the appendix. From the calculation of the difficulty level parameters in the RStudio software, good results are obtained as in table 13. Of the 25 items of the Arabic Language Midterm Exam or instruments that have been analyzed using RStudio software, it is found that the parameter value at the difficulty level for each item. Based on the table for each item, 5 items are classified as "difficult", 11 items are classified as "medium", and the remaining 9 items are categorized as "low or easy" difficulty. This study also uses a type of quantitative research. And to investigate the items tested to 10th grade students of Muhammadiyah Vocational High School (SMK) using a quantitative type of data grouping by analyzing the items of the Even Mid-Semester Exam, to determine the quality of the product used, a range of quantitative data is needed in the form of raw data and response values from multiple choice questions to be studied .